Pediatric Germ Cell Tumors Biology Treatment Survivorship - Frazier, A. Lindsay; Amatruda, James F.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Germ cell tumors are relatively rare compared with other malignancies, and compilations of knowledge that encompass the entire spectrum of the disease are lacking. This textbook, written by the foremost authorities in the field, rectifies the situation by discussing in depth a broad range of topics, including biology, epidemiology, pathology, treatment, and late effects. Bearing in mind that germ cell tumors are most prevalent in the adolescent and young adult age group, causes of disease and treatment approaches in pediatric and adult patients are compared and contrasted. By spanning the entire life course, from prenatal origins of disease through to treatment in adults and late effects of treatment, the editors have produced a book that will be of interest to both pediatric and adult oncologists.
Keywords: Medicine; Oncology; Pediatrics; Medicine & Public Health; Oncology; Pediatrics